Flag leaf nutrition for enhancing resource use efficiency in rice (Oryza sativa L.) - Surya M S (Department of agronomy, College of agriculture, 2015)
The experiment entitled “Flag leaf nutrition for enhancing resource use efficiency in rice (Oryza sativa L.)” was undertaken at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram, during June to October, 2014. The main objectives of the study were to at assess the effect of flag leaf foliar nutrition on partitioning of photosynthates, growth and productivity of rice and to work out the economics of the practice in lowland rice ecosystem. The field experiment comprised [(5x3)+1] treatment combinations, laid out in randomised block design with three replications, using PTB 52 (Aiswarya) as the test variety. The treatments were 0.5 per cent each of S1 : potassium nitrate, S2 : calcium nitrate, S3 : magnesium sulphate, S4 : 19 : 19 : 19 complex and S5 : a combination S2 + S3 + S4, sprayed at three crop growth stages viz., G1 : Booting stage, G2 : Booting + Flowering stages and G3 : Booting + Flowering + Milk stages, as compared against a control (KAU POP for medium duration rice). The flag leaf nutrition treatments (s1g1 to s5g3) were given, over and above the KAU POP. The effect of nutrient sources used for flag leaf nutrition (FLN) was more pronounced than the growth stages chosen for FLN. Flag leaf area was significantly higher at booting (4.98 cm2) and flowering stages (8.11 cm2) with S1 (potassium nitrate @ 0.5 %), which was at par with S4 (19: 19: 19 complex). Foliar spraying of potassium nitrate @ 0.5 per cent at booting and flowering stages (s1g2) recorded the highest flag leaf area (9.08 cm2) at flowering stage and s2g3 resulted in the highest flag leaf area (11.65cm2) at harvest stage. FLN had no significant effect on the number of days taken for panicle exsertion. Latent tiller production (2.78 hill-1) was significantly higher with potassium nitrate @ 0.5 %. The relative growth rate recorded at booting (0.174 mg g-1 day-1), flowering (0.057 mg g-1 day-1) and harvest stages (0.028 mg g-1 day-1) was also superior with potassium nitrate. Net assimilation rate (NAR) recorded at booting stage was significantly higher for potassium nitrate (3.76 mg cm-2 day-1). But at flowering stage, 19:19:19 complex had the same effect with a NAR of 2.58 mg cm-2 day-1. FLN with 19:19:19 complex (S4) registered significantly higher chlorophyll content (2.58 mg g-1) in flag leaf blade at flowering stage. However, the carotenoid content was significantly superior (1.83 mg g-1) with potassium nitrate. All the yield attributes viz. productive tiller count (490.19), grain weight panicle-1 (2.18 g), number of spikelets panicle-1 (89.11), filled grains panicle-1 and thousand grain weight (28.55 g) were significantly superior with (potassium nitrate @ 0.5 %) as compared to KAU POP which recorded 417.24 productive tillers m-2, 82.57 spikelets panicle-1, 1.43 g grain weight panicle-1 and a thousand grain weight of 21.51 g. Further, sterility percentage was the lowest (11.94 per cent) with S1 compared to KAU POP (16.05 per cent). The effect of potassium nitrate was at par with 19: 19: 19 complex, with respect to sterility percentage and thousand grain weight. FLN with potassium nitrate @ 0.5 per cent recorded significantly higher grain yield (5.95 t ha-1) followed by 19: 19: 19 complex (5.01 t ha-1). The treatment combination, s1g1 (potassium nitrate at booting stage) recorded the highest yield of 6.28 t ha-1. The KAU POP recorded a grain yield of 4.41 t ha-1. Straw yield was also significantly higher with potassium nitrate. Grain yield recorded with flag leaf nutrition at booting + flowering stages (G2) (4.52 t ha-1) and booting + flowering + milk stages (G3) (4.68 t ha-1) were at par. Grain to straw ratio (0.80) and harvest index (0.44) were superior with 19: 19: 19 complex @ 0.5 per cent. Index leaf (flag leaf) analysis recorded significantly higher N and P contents with S5 and K content with S1. The treatment s3g3 recorded the highest sulphur content in flag leaf. The treatment combination, s1g2 recorded significantly higher crude protein content (8.34 per cent) in grain. FLN had no effect on the incidence of pests and diseases. FLN with potassium nitrate @ 0.5 per cent (S1) recorded significantly higher N, P and K uptake. The treatment combination, s3g2 recorded significantly higher sulphur uptake. Nutrient use efficiency assessed in terms of nitrogen use efficiency, agronomic efficiency and apparent recovery efficiency were significantly higher with S1 followed by 19: 19: 19 complex. Gross income ( 1,35,127 ha-1), net income ( 70,102 ha-1) and benefit cost ratio (2.07) were significantly higher with S1, compared to KAU POP with a BCR of 1.65. The study revealed that KAU POP recommendation for high yielding medium duration wetland rice (FYM @ 5 t ha-1 + 90:45:45 kg NPK ha-1) supplemented with FLN of potassium nitrate @ 0.5 per cent concentration, 5 days prior to booting and 50 per cent flowering stages, resulted in significantly higher grain yield, nutrient use efficiency and profitability, in the rice variety Aiswarya. However, the photosynthate partitioning efficiency, assessed in terms of harvest index and grain to straw ratio were observed to be superior with 19:19:19 complex @ 0.5 per cent